The model of conjugate heat and mass transfer between a particle and a fluid flow in spray drying based on the boundary element method - GOMBOC, TIMI; ILJAŽ, JURIJ; ZADRAVEC, MATEJ; HRIBERŠEK, MATJAŽ (Anali PAZU, 2022)
Drying is one of the oldest process technologies, which is used in different industrial applications. Drying process is complex physical process that involves coupled multiphase heat, mass and momentum transfer. As for example by spray drying process, local drying conditions inside the dryer affect to total drying time of porous particles. For this reason, the influence between particle and drying gas is very important. Through the drying process heat and mass exchange between particles and drying gas occurs, which results in local change of drying conditions. Two-way interaction (drying air to particle and particle to drying air) need to be considered to obtain accurate results. Fully coupled model for heat and mass transfer between particles and drying gas on the base of the Boundary Elements Method was developed in the present work, were particles were modelled as points. The results presented in this work show that two-way coupling between particles and drying gas is important in order to provide accurate results.
Keywords: spherical particle; porous media; boundary element method; elliptic fundamental solution; spray drying; 1D approach